Effect of the pH on the Antibacterial Potential and Cytotoxicity of Different Plasma-Activated Liquids - Sampaio, Aline da Graça [UNESP]; Chiappim, William [UNESP]; Milhan, Noala Vicensoto Moreira [UNESP]; Botan Neto, Benedito; Pessoa, Rodrigo; Koga-Ito, Cristiane Yumi [UNESP] (MDPI, 2022)
In this study, different plasma-activated liquids were evaluated for their antimicrobial effects against Escherichia coli, as well as for their cytotoxicity on mammalian cells. The PALs were prepared from distilled (DIS), deionized (DI), filtered (FIL), and tap (TAP) water. Additionally, 0.9% NaCl saline solution (SAL) was plasma-activated. These PALs were prepared using 5 L/min air gliding arc plasma jet for up to 60.0 min of exposure. Subsequently, the physicochemical properties, such as, the oxidation-reduction potential (ORP), the pH, the conductivity, and the total dissolved solids (TDS) were characterized by a water multiparameter. The PALs obtained showed a drastic decrease in the pH with increasing plasma exposure time, in contrast, the conductivity and TDS increased. In a general trend, the UV-vis analyses identified a higher production of the following reactive species of nitrogen and oxygen (RONS), HNO2, H2O2, NO3−, and NO2−. Except for the plasma-activated filtered water (PAW-FIL), where there was a change in the position of NO2− and NO3− at some pHs, The higher production of HNO2 and H2O2-reactive species was observed at a low pH. Finally, the standardized suspensions of Escherichia coli were exposed to PAL for up to 60.0 min. The plasma-activated deionized water (PAW-DI pH 2.5), plasma-activated distilled water (PAW-DIS pH 2.5 and 3), and plasma-activated tap water (PAW-TAP 3.5) showed the best antimicrobial effects at exposure times of 3.0, 10.0, and 30.0 min, respectively. The MTT analysis demonstrated low toxicity of all of the PAL samples. Our results indicate that the plasma activation of different liquids using the gliding arc system can generate specific physicochemical conditions that produce excellent antibacterial effects for E. coli with a safe application, thus bringing future contributions to creating new antimicrobial protocols.
Keywords: antimicrobial effect; deionized water; distilled water; Escherichia coli; filtered water; gliding arc discharge; plasma-activated liquid (PAL); plasma-activated water (PAW); saline; toxicity